1998
DOI: 10.1152/ajprenal.1998.275.2.f239
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of ROMK expression in kidney cortex and medulla by aldosterone and potassium

Abstract: This study explores the role of K+ and aldosterone in the regulation of mRNA of the ATP-sensitive, inwardly rectifying K+ channel, ROMK, in the rat kidney. K+ deficiency downregulated ROMK mRNA in cortex to 47.1 ± 5.1% of control ( P < 0.001) and in medulla to 56.1 ± 3.4% ( P < 0.001). High-K+ diet slightly increased ROMK mRNA in medulla to 122 ± 9% ( P < 0.05 vs. control). Adrenalectomy (Adx) downregulated cortical ROMK mRNA to 30.7 ± 6.8% ( P < 0.001 vs. control), and increased it in medulla to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 18 publications
7
63
2
1
Order By: Relevance
“…Since aldosterone/MR activation is known to modulate ion channel expression in other tissues (16)(17)(18), we reasoned that KCa2.3 might be involved in aldosterone/MR-induced choroidal vasodilation. Immunolocalization showed that KCa2.3 expression in rat retinas was restricted to the endothelial cells of choroid vessels (Figure 2, A-C, and Supplemental Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Since aldosterone/MR activation is known to modulate ion channel expression in other tissues (16)(17)(18), we reasoned that KCa2.3 might be involved in aldosterone/MR-induced choroidal vasodilation. Immunolocalization showed that KCa2.3 expression in rat retinas was restricted to the endothelial cells of choroid vessels (Figure 2, A-C, and Supplemental Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been difficult to distinguish the individual roles of BK and ROMK channels with respect to secreting K in direct response to elevated K or increased aldosterone. In the CCD (27) and the CNT (28), ROMK is up-regulated in the apical membrane by a high K diet. Aldosterone increases ROMK in the apical membrane of the rat CCD (29).…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, entering CNT Na ϩ is close to 45 mM at baseline, and the impact on CNT K ϩ secretion with doubling of ROMK was on the order of 10%. This should not be taken to discount the significance of chronic dietary K ϩ in modulating ROMK expression (47), but it is outside the focus of the model calculations in this work. Of note, comparing FHH mice with control, there seemed to be little difference of ROMK expression on low-or high-K ϩ diets (20).…”
mentioning
confidence: 99%